Begging for change - Flake, Sharon (Disney Jump at the Sun, 2004)
Teenaged Raspberry Hill tries to sort out her confused feelings of disgust, shame, and love for her homeless, drug addicted father and worries that she may have inherited his lying and stealing ways.